American and European Perspectives in Understanding Digital Religion: A Critical Analysis - Subekti, Dendy; Suhermanto Ja’far; Noorafifah Binti Waipin (Kediri Journal of Journalism and Digital Media (KJOURDIA), 2026)
This article critically examines American and European academic perceptions of digital religion by addressing questions of minority religious community representation, identity construction, and power dynamics within digital environments. The research seeks to analyze how Western scholars interpret digital religion as a blend of online and offline religious activities, and the extent to which these concepts redefine understandings of minority religions and digital power. Employing a qualitative, critical methodology, the study compares the literature from Europe and North America using Critical Discourse Analysis (CDA). The analytical perspective draws from postcolonial theory, media anthropology, and the “third space” idea to investigate issues of acceptance, rejection, and digital freedom. The results highlight significant variation between the two traditions. The American academic community mostly singles out online religion as “networked religion,” pointing out community building, religious participation, and innovation enabled by digital media. On the other hand, European scholars adopt a more cautionary tone, focusing on mediatization, secularization, migration, nationalism, and the political consequences of the digital religious sector. The study further demonstrates how the digital world offers places filled with contradictions for religious minorities, giving them the opportunity to be seen, to work with their identity and to resist. Still, at the same time, these places also allow hate speech, emotional division, and inequality to be exacerbated. The article posits that digital religion must be seen not only as a technological innovation but also as an intricate cultural, political, and ethical realm that is deeply shaped by inclusive, interdisciplinary, and globally aware intervention in future research.